Perbandingan Ekologi Dan Peran Penting Belalang Gomphocerinae Dan Kumbang Ladybugs Dalam Pertanian Berkelanjutan - Refalia Clara Payow; Augustinus Robin Butarbutar (STIKES Columbia Asia Medan, 2024)
This study compares the morphological characteristics, habitat, behavior, ecology, and life cycle of Gomphocerinae grasshoppers and ladybugs, and examines their ecological and economic roles. Gomphocerinae, with their slender bodies and strong hind legs for jumping, are typically found in grasslands and fields as herbivores essential in the food chain. Conversely, ladybugs, with their rounded bodies and hard elytra, are found in various habitats such as gardens and forests and act as predators of small insects like aphids. The study finds that Gomphocerinae can become significant agricultural pests, while ladybugs are valued as biological control agents. Gomphocerinae undergo incomplete metamorphosis, whereas ladybugs undergo complete metamorphosis, showing unique evolutionary adaptations. A deep understanding of these species is crucial for ecosystem management and sustainable agriculture, supporting the reduction of chemical pesticide use and promoting environmentally friendly farming practices.